Design, Synthesis and Evaluation of a Series of 1, 5‐Diaryl‐1, 2, 3‐triazole‐4‐carbohydrazones as Inhibitors of the YAP‐TAZ/TEAD Complex. (1st July 2021) - Gibault, Floriane; Sturbaut, Manon; Coevoet, Mathilde; Pugnière, Martine; Burtscher, Ashley; Allemand, Frédéric; Melnyk, Patricia; Hong, Wanjin; Rubin, Brian P.; Pobbati, Ajaybabu V.; Guichou, Jean‐François; Cotelle, Philippe; et al.
Abstract: Starting from our previously reported hit, a series of 1, 5‐diaryl‐1, 2, 3‐triazole‐4‐carbohydrazones were synthesized and evaluated as inhibitors of the YAP/TAZ‐TEAD complex. Their binding to hTEAD2 was confirmed by nanodifferential scanning fluorimetry, and some of the compounds were also found to moderately disrupt the YAP‐TEAD interaction, as assessed by a fluorescence polarization assay. A TEAD luciferase gene reporter assay performed in HEK293T cells and RTqPCR measurements in MDA‐MB231 cells showed that these compounds inhibit YAP/TAZ‐TEAD activity to cells in the micromolar range. In spite of the cytotoxic effects displayed by some of the compounds of this series, they are still good starting points and can be suitably modified into an effective and viable YAP‐TEAD disruptor in the future. Abstract : Disruptors ! A series of 1, 5‐diaryl‐1, 2, 3‐triazole‐4‐carbohydrazones was synthesized and tested as inhibitors of the YAP‐TEAD complex. The structural features responsible for TEAD inhibition have been determined. A hit compound 53 emerged as a weak hTEAD2 binder with micromolar inhibition in a TEAD reporter assay (IC50 =1.7 μM, HEK293T cells) and a proliferation assay (CC50 =6.9 μM, MDA‐MB231 cells).